2009
DOI: 10.1093/tropej/fmp054
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a 5-year Programme to Prevent Mother-to-child Transmission of HIV Infection in Northern Uganda

Abstract: Prevention of mother-to-child transmission (PMTCT) is essential in HIV/AIDS control. We analysed 2000-05 data from mother-infant pairs in our PMTCT programme in rural Uganda, examining programme utilization and outcomes, HIV transmission rates and predictors of death or loss to follow-up (LFU). Out of 19,017 women, 1,037 (5.5%) attending antenatal care services tested HIV positive. Of these, 517 (50%) enrolled in the PMTCT programme and gave birth to 567 infants. Before tracing, 303 (53%) mother-infant pairs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
68
5
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 25 publications
11
68
5
2
Order By: Relevance
“…These results were similar to those reported from Uganda[21]. Furthermore, the ORWs reported that women were reluctant to remain in care due to the rude behavior of PMTCT providers at ICTC clinics, lack of sufficient staff, lack of testing kits for babies, and drug stock-outs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results were similar to those reported from Uganda[21]. Furthermore, the ORWs reported that women were reluctant to remain in care due to the rude behavior of PMTCT providers at ICTC clinics, lack of sufficient staff, lack of testing kits for babies, and drug stock-outs.…”
Section: Discussionsupporting
confidence: 85%
“…The ORWs reported that mothers were demotivated from bringing their babies for HIV testing due to lack of knowledge about baby’s HIV testing at four time points, lack of availability of testing kits, and lack of personnel trained to collect blood from babies for HIV testing. These results are consistent with those reported from South Africa [26] and Uganda [21]. Loss to follow up of HIV exposed infants is reported to be 29%, according to the Indian PMTCT program [27] A study in Nigeria [28] suggested the utility of cross-cutting interventions, including recruitment and retention of motivated healthcare workers in PMTCT implementation and training.…”
Section: Discussionsupporting
confidence: 84%
“…However, in sub-Saharan Africa, up to 81% of mother-baby pairs are not retained in care six months after delivery [8, 9]. In Uganda, loss to follow-up (LTFU) of mother-baby pair has been reported to be 53.4% [10]. Literature shows that the majority of mother-baby pairs who are not retained in eMTCT programmes are due to LTFU and not death [11], suggesting that the infants remain alive, but at higher risk of acquisition of HIV from their mother than infants who remain in care.…”
Section: Introductionmentioning
confidence: 99%
“…Se trata de una cifra muy elevada, muy superior a las de publicaciones similares sobre programas nacionales, bien implementados, que están en torno al 10-15%. Un trabajo en Uganda encontró una transmisión acumulada del 8% pero que aumentaba al 15% si se incluían los niños no confirmados fallecidos 16 . En Botswana, uno de los países donde se han realizado mayores esfuerzos en el control de la transmisión vertical de VIH, se han registrado tasas de infección del 7% 17 .…”
Section: Discussionunclassified